Marco conceptual para el diseño de una estrategia competitiva para la ciudad de Lima - Medianero Burga, David (2010)
The construction of a new index of competitiveness, by an international team led by Michael Porter, brings us back to a traditional debate in economics about the sources of economic growth and, in general, the analysis of the determinants of welfare. Based on recent advances in economic growth theory, Porter has built a conceptual framework that explains the prosperity from three generic factors: (i) the allocation of resources, a factor that includes not only natural resources like oil and gold, but also the geographic location and size of a country and its population, (ii) the macroeconomic competitiveness, a term under which we understand the factors that influence the productivity of enterprises, such as fiscal and monetary policy, basic infrastructure and legal institutions, and (iii) the microeconomic competitiveness, terms that encompasses the factors related to business strategy and development of clusters, among others. This paper offers a conceptual model for the development of strategic plans at the territorial level, based essentially on the proposal of Porter, from whom we have taken much of the sustainability concept. It also proposes a territorial economic analysis, which we have used in the initial diagnosis for the Lima region, in Peru.